2016
DOI: 10.12788/jcso.0227
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a nurse practitioner-led symptom clinic on emergency department use in cancer patients

Abstract: Te impact of a nurse practitioner-led symptom clinic on emergency department use in cancer patients E mergency department (ED) use and hospitalization across the continuum of cancer treatment are common and distressing issues for patients and their families. Use of these services is recognized as an indicator of poor quality end-oflife care, but studies have demonstrated frequent use of them in patients with advanced cancer and particularly in those who are close to the end of life. 1-3 Tere is growing evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…To date, multiple oncology programs have established a dedicated urgent care facility with some, [28][29][30][31][32][33][34][35][36][37][38][39][40] but not all, [41][42][43][44] publishing their infrastructure. While three represent satellite urgent care or observation units embedded within fully staffed, continuously operating, standalone cancer hospital EDs, 28,29,35 the remainder are dedicated clinics affiliated with either a cancer center or a large oncology practice that are simultaneously served by a general ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, multiple oncology programs have established a dedicated urgent care facility with some, [28][29][30][31][32][33][34][35][36][37][38][39][40] but not all, [41][42][43][44] publishing their infrastructure. While three represent satellite urgent care or observation units embedded within fully staffed, continuously operating, standalone cancer hospital EDs, 28,29,35 the remainder are dedicated clinics affiliated with either a cancer center or a large oncology practice that are simultaneously served by a general ED.…”
Section: Discussionmentioning
confidence: 99%
“…Scope of practice, however, spans the spectrum from moderate-to-high-acuity urgent care [30][31][32][33][34]39,41,42,44 to facilities limiting services to supportive care (eg, hydration and transfusions). 36,38,40 The Smilow OECC, however, is among the only three high-acuity sites where APPs are the primary providers 33,44 and is the only APP-driven site with extended hours 365 days of the year. Four high-acuity centers have applied robust statistical modeling to assess impact on ED utilization or hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…healthcare that focuses on optimal management of pain and other symptoms while incorporating psychosocial and spiritual care according to patient/family needs, values, beliefs and cultures.'' 1 This philosophy has been implemented in a variety of ways in oncology practices around the world [2][3][4][5][6][7][8][9][10][11][12][13][14] and has been shown to improve patient outcomes, including decreased symptom severity, improved quality of life, and in some cases, decreased utilization of emergency department (ED) and hospital admissions. [15][16][17] The study by Temel et al (2010) showed improvement in quality of life, and notably increased survival in patients with advanced lung cancer when palliative care was introduced early in the course of illness.…”
Section: Introductionmentioning
confidence: 99%
“…Sivendran et al examined a NP led, physician supervised, outpatient symptom review clinic for oncology patients in the ED. Although the primary population in this patient cohort were patients with advanced cancer undergoing chemotherapy, rather than HSCT recipients, 12.7% of patients presented with fever and were safely managed by the NP led clinics, with 95% of the patients presenting with acute symptoms, avoiding hospitalization 42. Hackett and Dowling evaluated the experiences of adult patients who had undergone lymphoma therapy through a nurse led consultative program.…”
mentioning
confidence: 99%